Peran PRO dalam Aktivitas Branding Universitas - Abdul Rohman (Jurnal Komunikasi, 2006)
In competitions era and declinations of public interest, university needs to do branding activities by using several communications media. One of them is public relations (PR). PR has special role in branding activities by its capabilities to build image and creates publicity. In order to run its role, increasing PR competences and dominant coalitions, related with PR position in management, are needed.